Pengaruh Kepemimpinan Dan Upah Kerja Terhadap Kinerja Karyawan Di Peternakan Telur Metro Lampung - Gunawan, Alfred; Defrizal, Defrizal (Journal of Information System, Applied, Management, Accounting and Research, 2024)
Performance is the result of a process that refers to and measures over a certain period of time based on previously established provisions or agreements. This research aims to find out whether leadership and wages influence employee performance at Metro Lampung egg farms. The population of this study were workers at Telur Metro Lampung. This research used a saturated sample so that the entire population of workers at Telur Metro Lampung was taken, totaling 38 people. The analytical method in this research is quantitative analysis using Multiple Linear Regression analysis, coefficient of determination test, t test and F test. Based on theoretical studies and data analysis results, it can be concluded that (1) The results of the hypothesis t test state that leadership has a significant effect on employee performance at Metro Lampung egg farms. (2) The results of the hypothesis t test state that work wages significantly influence employee performance at the Metro Lampung egg farm. (3) The results of the hypothesis F test state that leadership and work wages jointly influence employee performance at the Metro Lampung egg farm.